Effects of deuteron optical models on the cross-section calculations of deuteron induced reactions on natural germanium. (October 2021) - Şekerci̇, M.; Özdoğan, H.; Kaplan, A.
Abstract: A common feature of scientific studies is that when experimental observation data are not available, theoretical calculations are used to obtain information about the subject under investigation. In this context, many parameters and theoretical models have been developed that can be used in nuclear physics studies just as it is in other branches of sciences. It is intended that by doing so, theoretical models can be improved using recent experimental data while also learning about outcomes where experimental data is unavailable or difficult to access. Among the many theoretical models available, there are also deuteron optical models whose effects are examined in this study. The objective of this study is to examine the effects of different deuteron optical models on the cross-section calculations of deuteron induced reactions on natural germanium. The cross-section values of nat Ge(d, x) 70 As, nat Ge(d, x) 71 As, nat Ge(d, x) 72 As, nat Ge(d, x) 73 As, nat Ge(d, x) 74 As and nat Ge(d, x) 76 As reactions were calculated using five deuteron optical models in the TALYS code's v1.95 for this aim, and the results were compared to the experimental data available in the database known as Experimental Nuclear Reaction Data (EXFOR) library. Graphics and quantitative analyses were also used to present the findings and interpretations of the outcomes. Highlights: -Cross-section calculations were done for natGe(d, x)70, 71, 72, 73, 74, 76As reactions by using different deuteron optical models. TALYS 1.95 code was used for the calculations. Obtained calculation results and available experimental data from the literature were compared.